Circulating innate lymphoid cells are dysregulated in patients with prostate cancer - Daniela Claudia Maresca; Evelina La Civita; Benedetta Romano; Maria Rosaria Ambrosio; Fabio Somma; Tania Wyss; Bernardo Rocco; Valentina Rubino; Luigi Cari; Philippe Krebs; Antonio Rodriguez-Calero; Matteo Ferro; et al. (Cellular & Molecular Biology Letters)
Abstract Background Prostate cancer (PCa) is the second most common cancer affecting men globally, especially those aged 50 years and above. Despite substantial progress in terms of both prognosis and therapy, PCa remains a significant health concern, necessitating the identification of novel therapeutic targets. Innate lymphoid cells (ILCs) have emerged as critical modulators of tumor immunity, exhibiting both pro- and antitumoral effects. However, little is known yet about their contribution in PCa. This study investigated the phenotypic and functional profiles of ILC subsets in the peripheral blood mononuclear cells (PBMCs) of patients with PCa stratified by Gleason score. Methods PBMCs were isolated by Lymphoprep. ILC frequency and activity were evaluated by flow cytometry. The levels of ILC-activating cytokines were analyzed by multiplex assay in the serum of healthy donors (HDs) and patients with PCa. To evaluate the crosstalk between ILC2s and cancer cells, PC3 and DU145 human PCa cell lines were used. Results We found a stage-dependent increase in the protumoral ILC2 frequency and a concurrent decrease in antitumoral ILC1s in patients with PCa compared with healthy controls. Interestingly, the frequency of ILC2s was higher in patients with elevated prostate-specific antigen (PSA) values, suggesting their potential as molecular predictor for defining the risk category of patients with PCa at diagnosis. Importantly, patients with PCa exhibited hyperactivated ILC2s, characterized by elevated interleukin (IL)-13 and IL-5 production, while ILC1s displayed reduced tumor necrosis factor (TNF)-α and interferon (IFN)-γ secretion. Furthermore, serum levels of ILC2-activating cytokines IL-33, IL-18, and prostaglandin D2 (PGD2) were elevated in patients with PCa. In vitro co-culture experiments demonstrated that PCa cell lines, capable of secreting these cytokines, could directly enhance ILC2 activity. Likewise, ILC2-derived IL-13 promoted PCa cell migration and invasion. Conclusions Collectively, our findings highlight a dysregulated ILC profile in PCa, characterized by ILC2 dominance and heightened activity at the expense of ILC1s, suggesting both ILC1s and ILC2s as potential therapeutic targets for PCa treatment. Graphical Abstract